Undergraduate exposure to patient presentations on the acute medical placement: a prospective study in a London teaching hospital - Amir H Sam; Chee Yeen Fung; Emilia Peleva; Zhin Ming Tan; Adam Savage; Mahdi Rahim; Fatima Osman; Mohammed Adnan (BMJ Open)
Objectives To identify the availability and variability of learning opportunities through patient presentations on an acute medical placement at a teaching hospital.Design A prospective study evaluating all acute admissions to the Acute Medical Unit over 14 days (336 hours). Clinical presentations and the day and time of admission were recorded and compared with the learning outcomes specified in the medical school curriculum.Setting An Acute Medical Unit at a London teaching hospital.Outcomes (1) Number of clinical presentations to the Acute Medical Unit over 14 days and (2) differences between the availability and variation of admissions and presentations between in-hours and out-of-hours.Results There were 359 admissions, representing 1318 presentations. Of those presentations, 76.6% were admitted out-of-hours and 23.4% in-hours. Gastrointestinal bleeding, tachycardia, oedema and raised inflammatory markers were over three times more common per hour out-of-hours than in-hours. Hypoxia was only seen out-of-hours. Important clinical presentations in the curriculum such as chest pain and hemiparesis were not commonly seen.Conclusions There is greater availability of presentations seen out-of-hours and a changing landscape of presentations seen in-hours. The out-of-hours presentation profile may be due to expanded community and specialist services. Medical schools need to carefully consider the timing and location of their clinical placements to maximise undergraduate learning opportunities.